Towards permeable boundaries of organizations? - Ringel, Leopold; Hiller, Petra; Zietsma, Charlene (Research in the sociology of organizations ;, 2018)
The classical concept of organizations as comprising solitary 'walled-in' actors with clear operational boundaries is increasingly being challenged. On the one hand, established organizational forms have been supplemented by a whole variety of new ones that only partially exhibit their properties and that frequently embed single organizations in national or transnational networks; furthermore, it is often not clear who the members of an organization are and what membership actually means, as in the case of new companies such as Uber or AirBnB, and even traditional organizations, such as universities, are undergoing drastic changes. On the other hand, organizations face increasing demands for transparency, meaning they have to disclose more and more information, which is supposed to engender less corruption, more efficiency, and more legitimacy. This volume investigates the impact of these changes on organizations and offers conceptual as well as empirical insights. Divided into four parts this volume examines concepts of organizational boundaries, boundaries and organizational dynamics, meta organization and organizational networks, and boundaries and organizational fields.